2004
DOI: 10.1021/ic049029k
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Ferrous α-Verdoheme−Cytochrome b5 Complex

Abstract: The ferrous alpha-verdoheme-cytochrome b(5) complex, [Fe(II)(verdoheme)](+), has been prepared and characterized spectroscopically. Anaerobic addition of excess sodium dithionite to [Fe(II)(verdoheme)](+) at pH 10 produces a one-electron-reduced species with spectroscopic characteristics that suggest a ferrous hexacoordinated verdoheme pineutral radical best formulated as a [Fe(II)(verdoheme*)] --> [Fe(I)(verdoheme)] resonance hybrid. At lower pH values (7.0 and 8.0) the one-electron-reduced species is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…5B). The g values obtained agreed with those reported for π-neutral radical species of bispyridine-bound ferrous verdoheme dimethyl ester in dimethylformamide/pyridine (6:4) solution at 163 K (g ⊥ = 2.002 and g // =1.937) [22] and those of ferrous verdoheme complexed with cytochrome b 5 at 90 K (g = 2.02, 2.00, and 1.925) [35]. Thus we concluded that the paramagnetic species generated in the rHO-1 system is a π-neutral radical of CO-bound ferrous verdoheme, [Fe II (verdoheme•)], complexed with rHO-1.…”
Section: Spectral Changes Of the Verdoheme-rho-1 Complex In The Nadphsupporting
confidence: 86%
See 3 more Smart Citations
“…5B). The g values obtained agreed with those reported for π-neutral radical species of bispyridine-bound ferrous verdoheme dimethyl ester in dimethylformamide/pyridine (6:4) solution at 163 K (g ⊥ = 2.002 and g // =1.937) [22] and those of ferrous verdoheme complexed with cytochrome b 5 at 90 K (g = 2.02, 2.00, and 1.925) [35]. Thus we concluded that the paramagnetic species generated in the rHO-1 system is a π-neutral radical of CO-bound ferrous verdoheme, [Fe II (verdoheme•)], complexed with rHO-1.…”
Section: Spectral Changes Of the Verdoheme-rho-1 Complex In The Nadphsupporting
confidence: 86%
“…3B). A similar species showing absorption peaks at 454 and 497 nm has been reported as a two-electron reduced form, [Fe II (verdoheme:)] − , in the reduction of verdoheme reconstituted with apocytochrome b 5 at pH 7.0 and 8.0 [35]. Thus we judged that the one-electron reduced π-neutral radical, [Fe II (verdoheme•)], of CO-bound ferrous verdoheme in complex with rHO-1 was generated first, followed by formation of the two-electron reduced species, [Fe II (verdoheme:)] − .…”
Section: Electrochemical Reduction Of Co-bound Verdoheme-rho-1 Complexsupporting
confidence: 69%
See 2 more Smart Citations
“…This redox reaction was only partially reversible (data not shown), probably due to a reaction leading to nonproductive decomposition of verdoheme, that does not lead to biliverdin [8]. While the immediate product of the reaction has yet to be characterized, a two-electron-reduced anion form of ferrous verdoheme has been indicated as a possible candidate [32]. Indeed, applying potentials below −0.60 V vs NHE caused further spectral changes, and this over-reduction was completely irreversible (data not shown).…”
Section: Electrochemical Reduction Of Verdoheme-rho-1 Complex Under Amentioning
confidence: 99%